Civil society briefs Vanuatu. (Metro Manila, Philippines Asian Development Bank, 2017)
The ADB has been working with Vanuatu since 1981 and In 2016, opened an extended mission in Vanuatu, further strengthening ADB in-country presence. ADB-supported activities involving civil society in Vanuatu include supporting the preparation of the National Sustainable Development Plan and the Vanuatu Women Development Scheme (VANWODS). ADB has been supporting VANWODS to upgrade its institutional capacity and governance arrangements. Following Cyclone Pam, support focused on rebuilding and restoring VANWODS facilities and equipment to enable its operations to continue following the cyclone. ADB in Vanuatu is also involved with the Coral Triangle Initiative.
Keywords: Public administration; Sustainable development; Electronic books